Bactericidal Activity of TiO2 on Cells of Pseudomonas aeruginosa ATCC 27853 - J. L. Aguilar Salinas; J. R. Pacheco Aguilar; S. A. Mayén Hernández; J. Santos Cruz (International Journal of Photoenergy)
The photocatalytic activity of semiconductors is increasingly being used to disinfect water, air, soils, and surfaces. Titanium dioxide (TiO2) is widely used as a photocatalyst in thin films, powder, and in mixtures with other semiconductors or metals. This work presents the antibacterial effects of TiO2 and light exposure (at 365 nm) on Pseudomonas aeruginosa ATCC 27853. TiO2 powder was prepared from a mixture of titanium isopropoxide, ethanol, and nitric acid using a green and short time sol-gel technique. The obtained gel annealed at 450°C was characterized by X-ray diffraction, Raman spectroscopy, ultraviolet-visible spectroscopy, diffuse reflectance, scanning electron microscopy, and transmission electron microscopy. The nanocomposite effectively catalyzed the inactivation of Pseudomonas aeruginosa. Following 90 minutes exposure to TiO2 and UV light, logarithm of cell density was reduced from 6 to 3. These results were confirmed by a factorial design incorporating two experimental replicates and two independent factors.